Automated synthesis and quality control of [99mTc]Tc-PSMA for radioguided surgery (in a [68Ga]Ga-PSMA workflow) - Else A. Aalbersberg; Lotte van Andel; Martine M. Geluk-Jonker; Jos H. Beijnen; Marcel P. M. Stokkel; Jeroen J. M. A. Hendrikx (SpringerOpen, 2020)
Abstract Background Lymph node dissection is a therapeutic option for prostate cancer patients with a high risk of- or proven lymph node metastases. Radioguided surgery after intravenous injection of [99mTc]Tc-PSMA could improve the selectivity of lymph node dissection. The aim of this project was to develop an automated synthesis method for [99mTc]Tc-PSMA, using the disposables and chemicals used at our institute for [68Ga]Ga-PSMA labeling. Furthermore, quality control procedures and validation results of the automated production of [99mTc]Tc-PSMA conform cGMP and cGRPP are presented. Methods [99mTc]Tc-PSMA is produced fully automatic with a Scintomics synthesis module. Quality control procedures are described and performed for: activity, labeling yield, visual inspection, pH measurement, sterility and endotoxin determination, radionuclide purity, radiochemical purity (99mTc-colloids, unbound [99mTc]pertechnetate, and other impurities), and HEPES content. Three batches of [99mTc]Tc-PSMA were prepared on three separate days for validation and stability testing at 0, 4, 6, and 24 h. Results [99mTc]Tc-PSMA can be successfully manufactured automatically within a [68Ga]Ga-PSMA workflow with the addition of only [99mTc]pertechnetate and stannous chloride. The radiochemical purity after production was highly reproducible (96.3%, 97.6%, and 98.2%) and remained > 90% (required for patient administration) up to 6 h later. Conclusion A fully automated labeling procedure with corresponding quality control methods for production of [99mTc]Tc-PSMA is presented, which is validated according to cGMP and cGRPP guidelines and can be implemented in a GMP environment. The produced [99mTc]Tc-PSMA is stable for up to 6 h. The presented procedure is almost identical to the automated production of [68Ga]Ga-PSMA and can therefore be implemented expediently if a workflow for [68Ga]Ga-PSMA is already in place.